HOTS Assessment Development to Assess High School Physics Problem-Solving Skills - Veni Wahyuni; Ratnawulan; Fatni Mufit (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop an assessment instrument based on Higher Order Thinking Skills (HOTS) to assess high school students' problem-solving abilities in the subject of physics on renewable energy using the Plomp development model. The study was conducted through three main stages, namely (1) preliminary research to analyze needs (2) prototyping phase to design and validate the assessment instrument, and (3) assessment phase to conduct limited trials and product revisions. The assessment instrument was developed by containing essay questions based on real contexts that require critical, analytical, and creative thinking skills. The results of expert validation showed that the assessment was in the valid category with an average percentage score of 0.93. Trials on high school students showed that the assessment was able to measure variations in problem-solving abilities more comprehensively. Thus, this HOTS assessment based on the Plomp model is effective for evaluating physics problem-solving abilities.